Design and Evaluation of a Decision Support System for Classifying Tourism Site Crowding and Recommending Governance Responses in Bunaken National Park - Aditya Kalua; Mochamad Agung Wibowo; Luther Alexander Latumakulita (Lembaga Riset dan Inovasi Almatani, 2026)
Effective governance of marine protected areas (MPAs) requires reliable mechanisms to translate multidimensional ecological and social data into coordinated institutional action. Despite widespread adoption of carrying capacity frameworks, a significant